The Role of Islamic Theology in Realising a Sustainable Islamic Economy - Muhammad Fitrah Insani; Hendra Syahputra (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
In an increasingly complex era of economic globalization, an understanding of the ethical values and principles of Islamic economics is becoming increasingly relevant. One of the principles of Islamic economics is ethics and kalam science. The science of Kalam not only plays a role in theological discourse but also contains ethical guidelines that are important in economic activity. The purpose of this research is to find out with the aim of identifying how the ethics contained in Kalam science can be the foundation for a sustainable Islamic economic system. The method used by researchers is a qualitative approach method with descriptive analysis of ethical concepts in Kalam science and its application as a basis for Islamic economic development. The results showed that ethics in Kalam science, such as honesty, justice, and social responsibility, are the main basis for Islamic economic development. The application of these values in Islamic economics helps to create social justice, avoid exploitation, and support the welfare of society through the mechanism of zakat, infaq, and sadaqah.